One United People : The Federalist Papers and the National Idea - Millican, Edward (Book collections on Project MUSE., 1990)
The Federalist and the Constitution, whose cause it defended, were created amid the turmoil of political controversy. Alexander Hamilton, James Madison, and John Jay, authors of The Federalist, were not theorists but fervent partisans in a campaign to gain acceptance -- by no means a sure thing at that time -- for the new plan of national government which they themselves had largely shaped. Their essays were immediately popular, were quickly collected and reissued in book form, and soon came to be recognized in America and Europe as a landmark in political theory -- the basic blueprint for th.